Seasonal changes in match demands and workload distribution in collegiate soccer across two seasons - Floersch, S.; Vidden, C.; Askow, A. T.; Jones, M. T.; Fields, J. B.; Jagim, A. R. (The Journal of Strength and Conditioning Research, 2024)
The purpose of this study was to examine seasonal changes in match demands in a collegiate women's soccer team. Forty-eight NCAA Division III women soccer athletes (age: 19.5 ± 1.2 years; height: 1.67 ± 0.05 m; body mass: 64.8 ± 7.4 kg; fat-free mass: 50.0 ± 4.5 kg; body fat %: 22.6 ± 6.0) were equipped with wearable global positioning systems with inertial sensors and heart rate (HR) monitors during matches throughout the 2019 (n = 22) and 2021 seasons (n = 26). Players were classified by position: flank player (FP; n = 28), center midfielder (CM; n = 11), and center back fielder (CB; n = 9) and as starters (S, n = 17) or reserves (R, n = 31). Variables included HR, training load, total distance, high-speed distance, distance per minute, and weighted distance. Differences in match and practice session demands were analyzed using linear mixed-effects models with season (2 levels; 2019 and 2021) as a fixed factor, with alpha set to p = 0.05. Data across all matches and training sessions were collapsed and presented as mean ± SD for descriptive purposes and then grouped by session type (i.e., match or training) and position. Athletes traveled more distance at high speeds during match play in the 2021 season compared with 2019 (mean difference, 95% confidence intervals [CI]) (200, 95% CI: 104, 304 km; p < 0.05) but had a lower training load in 2021 compared with 2019 (-50, 95% CI: -63, -36; p < 0.05) during match play. For training sessions, mean HR (4, 95% CI: 2, 5 bpm), total distance (0.5, 95% CI: 0.4, 0.7), distance per minute (5.6, 95% CI: 4.5, 6.7 m·min-1), high-speed distance (43, 95% CI: 43, 18, 67 m), high accelerations (8.6, 95% CI: 5.4, 11.8 n), and high accelerations per minute (0.1, 95% CI: 0.1, 0.1 n·min-1) were all higher in 2021 compared with 2019 (p < 0.05). As a team, several differences in measures of external workload were found between seasons in both session types (training and matches). Variations in positional demands of match play appear to fluctuate by year.